Damage Formation and Calculation of Energy Loss during Implantation of Antimony and Boron Ion in Silicon Target (Journal of Nepal Physical Society, 2019)
The aim of this research work is a computational study of damage profile and visualization of the ion implantation graph obtained from the simulation method using SRIM-2013 software. SRIM (Stopping and Range of Ions in Matter) helps in calculating the energy required for an ion to obtain maximum concentration for desirable range and TRIM (Transport of Ions in Matter) is used to calculate doping statistics and calculation of energy loss. The main objective of this work is to get knowledge about the graphical study of ion range, distribution, stopping power and energy loss during implantation of antimony and boron ion on the silicon target within 0 to 3500 Å target depth. The implantations of 10,000 antimony and boron ions are accelerated by 350 keV and 45 keV energy in silicon monolayer target to obtain maximum defects concentration. The result of the ionization process indicates that 11.68% of the total energy of antimony ion and 65.25% of the total energy of boron ion are lost during the ionization process. This indicates that lighter boron ion causes more ionization than the heavier antimony ion for the same projected range.